The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s13311-021-01020-x
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep Disturbances Associated with Neurological Autoimmunity

Abstract: Associations between sleep disorders and neurological autoimmunity have been notably expanding recently. Potential immune-mediated etiopathogenesis has been proposed for various sleep disorders including narcolepsy, Kleine-Levin syndrome, and Morvan syndrome. Sleep manifestations are also common in various autoimmune neurological syndromes, but may be underestimated as overriding presenting (and potentially dangerous) neurological symptoms often require more urgent attention. Even so, sleep dysfunction has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 174 publications
(348 reference statements)
0
8
0
Order By: Relevance
“…34 And associations between various sleeping disorders and neurological autoimmunity have been notably reported, also sleeping manifestations were common in autoimmune neurological syndromes. 35 Studies about celiac disease showed anti-neuronal antibodies to CNS was higher with neurological symptoms than without neurological symptoms. 36 Anxiety and depression were very common in functional gastrointestinal disorders, we tried to find the relationship between anti-neuronal antibodies with anxiety and depression in IBS patients but the correlation was negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 And associations between various sleeping disorders and neurological autoimmunity have been notably reported, also sleeping manifestations were common in autoimmune neurological syndromes. 35 Studies about celiac disease showed anti-neuronal antibodies to CNS was higher with neurological symptoms than without neurological symptoms. 36 Anxiety and depression were very common in functional gastrointestinal disorders, we tried to find the relationship between anti-neuronal antibodies with anxiety and depression in IBS patients but the correlation was negative.…”
Section: Discussionmentioning
confidence: 99%
“…Serum and cerebrospinal fluid anti‐neuronal antibodies were detected in patients with headache with neurological deficits 34 . And associations between various sleeping disorders and neurological autoimmunity have been notably reported, also sleeping manifestations were common in autoimmune neurological syndromes 35 . Studies about celiac disease showed anti‐neuronal antibodies to CNS was higher with neurological symptoms than without neurological symptoms 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbances: Sleep disturbances are also common in patients with AE[ 41 ]. Sleep dysfunctions have also been described in association with various neuron-specific antibody biomarkers, including IgLON5, LGI1, CASPR2, NMDA receptor, and Ma2.…”
Section: Discussionmentioning
confidence: 99%
“…18 Sleep disturbance is a medical disorder of sleep patterns and the most signi cant cause of multiple psychological disorders and somatic diseases. [19][20][21] The early identi cation of nurses at higher risk of sleep disturbances is critical to nursing career development. Gender, age, anxiety, night shift, etc have identi ed multiple predictors to signi cantly correlated with sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%